Centennial city: the City of Auckland model - Hill, Marguerite (Architectural History Aotearoa, 2024)
Auckland Council is lucky to care for the surviving portion of a city model made for the New Zealand Centennial Exhibition in 1940. The model represents a section of Auckland central, covering the area from Albert Park to Nelson Street, and Waitematā Harbour to what is now Aotea Square. The model was displayed in Dominion Court, one of a dozen models which represented New Zealand's main cities and towns. Fletchersʹ architects Ronald Muston and Lewis Walker were responsible for the design of Dominion Court and the interpretive models and dioramas within. Muston had a special interest in the models and even travelled to Hollywood to learn about current trends in movie model design and advertising techniques. The ingenuity of the model makers included ships that ʺsailedʺ on the harbours, faux glow worms in the papier mâché Waitomo Caves, and a model of Aoraki/Mount Cook which was over 7.5m high. Thousands of wooden model buildings were made and hand‐painted by artists and technical college students and were based on aerial and street‐level photographs and specific colour palettes for each city. The model came to Auckland City Council after the exhibition closed and has been displayed inside and outside of council. It was recently conserved and is once again on public display.